A blueprint to build women chief executive officers globally. (28th May 2018) - Rao, M.S.
Abstract : The purpose of this article is to offer a blueprint to build women chief executive officers (CEOs) globally. It outlines essential qualities for women CEOs. It explains CEO acumen and offers tools and techniques for women to excel as CEOs. It draws a blueprint for global organizations to build women CEOs. It differentiates between women and men leaders. It emphasizes women can make better leaders than men. It illustrates with inspiring examples of women leaders including Melinda Gates, Michelle Obama, Hillary Clinton, Angela Merkel, Indra Nooyi, Ursula Burns, Meg Whitman, and Sheryl Sandberg. It implores women to seize the opportunities to break the glass ceiling to excel as CEOs. It enlightens the society cannot grow when one sex is denied with opportunities. It calls upon men to empathize with women and extend their hands with a big heart to groom them as CEOs. It advocates gender equality globally. It concludes women leaders must express their ambition in the early stage of their careers and work hard consistently and relentlessly with a focus and vision to excel as CEOs globally.